2008
DOI: 10.1002/jpln.200700331
|View full text |Cite
|
Sign up to set email alerts
|

The significance of organic‐anion exudation for the aluminum resistance of primary triticale derived from wheat and rye parents differing in aluminum resistance

Abstract: Eight primary octoploid triticale genotypes (xTriticosecale Wittmack) derived from four wheat cultivars (Triticum aestivum L.) and two rye inbred lines (Secale cereale L.) differing in aluminum (Al) resistance were investigated with respect to their response to Al supply. Aluminum‐induced inhibition of root elongation (48 h, 25 µM Al supply), callose formation, and the accumulation of Al in root tips (4 h, 25 µM Al supply) were used as parameters to assess Al resistance. Using these parameters, the existing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The current study provides a detailed characterization of citrate efflux from wheat roots. We have extended the work of Stass et al (2008) by demonstrating that citrate efflux actually occurs constitutively in Carazinho and several other highly Alresistant Brazilian cultivars. This finding contrasts with the citrate efflux characterized in other cereal species such as barley, sorghum, and maize where the citrate efflux is activated by Al in much the same way that malate efflux is activated from Al-resistant wheat plants (Pellet et al, 1995;Furukawa et al, 2007;Magalhaes et al, 2007).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The current study provides a detailed characterization of citrate efflux from wheat roots. We have extended the work of Stass et al (2008) by demonstrating that citrate efflux actually occurs constitutively in Carazinho and several other highly Alresistant Brazilian cultivars. This finding contrasts with the citrate efflux characterized in other cereal species such as barley, sorghum, and maize where the citrate efflux is activated by Al in much the same way that malate efflux is activated from Al-resistant wheat plants (Pellet et al, 1995;Furukawa et al, 2007;Magalhaes et al, 2007).…”
Section: Discussionmentioning
confidence: 63%
“…Our results demonstrate that Al resistance is a multigenic trait in some genotypes and that these genes do not necessarily act by modifying the function of TaALMT1. Stass et al (2008) first reported citrate efflux from the roots of Carazinho while investigating the Al resistance of triticale. They found that citrate was activated by Al treatment and that the wheat parent could influence the Al resistance of progeny from wheat/ Figure 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of organic acid anions secreted was correlated positively with relative root elongation and negatively with Al content in root apices under Al stress, suggesting that the secretion of malate and citrate seems to be involved with the exclusion of Al from root tips. Eight primary octoploid triticale genotypes derived from four common wheat cultivars and two rye lines differing in Al tolerance were tested for Al tolerance (Stass et al 2008). It was concluded that the degree of Al tolerance of the triticale genotypes was closely related to the Al-induced citrate exudation, which was mainly controlled by the tolerance of the wheat parent.…”
Section: Mineral Toxicitymentioning
confidence: 99%
“…Recently, it has been also identified that the N-domain of TaALMT1 mediates ion transport even in the absence of the C-domain (Ligaba et al 2013). Other homologues of TaALMT1 such as AtALMT1 from Arabidopsis thaliana (Hoekenga et al 2006), BnALMT1 and BnALMT2 from rape (Brassica napus; Ligaba et al 2006), and ScALMT1 from rye (Seceale cereale; Li et al 2000;Stass et al 2008) have been identified that confer Al-activated malate efflux (Table 2.2).…”
Section: Al-activated Malate Effluxmentioning
confidence: 99%